Evaluation of the necessity of routine histopathological examination in tonsillectomy and/or adenoidectomy operations (Annals of Medical Research, 2023)
Aim: The aim of the study is to discuss the necessity of microscopic histopathological examination for routine tonsillectomy and/or adenoidectomy (T&A).Materials and Methods: Patients who underwent T&A surgery in our clinic between 2017 and 2022 and were diagnosed pathologically were included in the study. The files of the patients were scanned retrospectively from the hospital automation system. Demographic characteristics (age, gender) and histopathological findings of the patients were recorded.Results: A total of 635 cases were analyzed, of which 294 were female (46.3%) and 341 were male (53.7%). The mean age of the patients was 12.6±7.1 years, and their ages ranged from 3 to 48 years. As a result of histopathological evaluation, the most common diagnosis was chronic lymphoid hyperplasia. No malignancy or unexpected findings were found in any of the samples.Conclusion: Given the rarity of unexpected clinical diagnoses in routine T&A specimens, it is difficult to justify the cost and effort of histopathologically analyzing each specimen. Therefore, the histopathological request for T&A specimens should be based on specific risk factors.